Hyperphosphatemia induces cellular senescence in human aorta smooth muscle cells through integrin linked kinase (ILK) up-regulation. (December 2015) - Troyano, Nuria; Nogal, María del; Mora, Inés; Diaz-Naves, Manuel; Lopez-Carrillo, Natalia; Sosa, Patricia; Rodriguez-Puyol, Diego; Olmos, Gemma; Ruiz-Torres, María P.
Graphical abstract: Highlights: Hyperphosphatemia induces senescence in vascular smooth muscle cells. Hyperphosphatemia-dependent senescence is due to increased IGF-1 and ILK signaling. Aged mice show high serum phosphate concentration linked to increased ILK expression. High serum phosphate links with higher senescence genes and ILK expression in vivo. ABSTRACT: Aging is conditioned by genetic and environmental factors. Hyperphosphatemia is related to some pathologies, affecting to vascular cells behavior. This work analyze whether high concentration of extracellular phosphate induces vascular smooth muscle cells senescence, exploring the intracellular mechanisms and highlighting the in vivo relevance of this phenomenon. Human aortic smooth muscle cells treated with β-Glycerophosphate (BGP, 10 mM) suffered cellular senescence by increasing p53, p21 and p16 expression and the senescence associated β-galactosidase activity. In parallel, BGP induced ILK overexpression, dependent on the IGF-1 receptor activation, and oxidative stress. Down-regulating ILK expression prevented BGP-induced senescence and oxidative stress. Aortic rings from young rats treated with 10 mM BGP for 48 h, showed increased p53, p16 and ILK expression and SA-β-gal activity. Seven/eight nephrectomized rats feeding a hyperphosphatemic diet and fifteenth- month old mice showed hyperphosphatemia and aortic ILK, p53 and p16 expression. In conclusion, we demonstrated that high extracellular concentration of phosphate induced senescence in cultured smooth muscle through the activation of IGF-1 receptor and ILK overexpression and provided solid evidences for the in vivo relevance of these results since aged animals showed high levels of serum phosphate linked to increased expression of ILK and senescence genes.